AL-FARABI AND IBN SINA'S CLASSIFICATION OF THE FOUNDATIONS OF THE THEORY OF "IYKUT" METHODS IN ORIENTAL MUSIC EDUCATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Farobi was a great philosopher of his time, and his views, which earned the title of "second teacher" after Aristotle among Eastern thinkers, are also important in the conditions of our independence.